Role of sociodemographic, obstetric history and planning for pregnancy in predicting short interpregnancy interval among antenatal mothers in Klang - Omar, Mardiana; Mohd. Zulkefli, NorAfiah; Ahmad, Norliza (Malaysian Medical Association, 2019)
Introduction: Short Interpregnancy interval (IPI) is definedas the interval between the live birth outcome and the next pregnancy conception of less than 24 months. It has been linked to adverse maternal and perinatal outcomes. The objective of this study was to determine the prevalence and the predictors of short IPI among antenatal mothers. Methods: A cross-sectional study was conducted among 452 antenatal mothers attending health clinics in Klang in April 2018. Probability sampling was used and data was collected by using a validated self-administered questionnaire. The dependent variable of the study was short IPI and the independent variables were sociodemographic, obstetric history and planning of pregnancy. Analysis of data collected in the study was performed by using IBM Statistical Package for Social Science (SPSS) version 24. Results: The prevalence of short IPI found in this study was48%. Seven identified predictors of short IPI were: age less than 25 years old (Adjusted Odd Ratios; AOR 12.16, 95%CI:4.72, 31.30), age of 26 to 30 years old (AOR 5.20, 95%CI: 2.62,10.32), age of 31 to 35 years old (AOR 2.90, 95% CI: 1.50,5.64), higher education (AOR 2.11, 95% CI: 1.34, 3.34), parity more than three (AOR 3.12, 95% CI: 1.42, 6.84), irregular menstruation (AOR 2.17, 95% CI: 1.40, 3.37) and unintended pregnancy (AOR 2.88, 95% CI: 1.88, 4.40). Conclusion: Innovative programmes, for example by making IPI information available through online resources, could effectively target young mothers as the younger generation prefers quick, easily-accessible and reliable information.